2020
DOI: 10.1038/s41416-020-01060-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on survival in patients with colorectal cancer: systematic review and meta-analysis of randomised controlled trials

Abstract: Background Low circulating vitamin D levels are associated with poor colorectal cancer (CRC) survival. We assess whether vitamin D supplementation improves CRC survival outcomes. Methods PubMed and Web of Science were searched. Randomised controlled trial (RCTs) of vitamin D supplementation reporting CRC mortality were included. RCTs with high risk of bias were excluded from analysis. Random-effects meta-analysis models calculated estimates of survival benefit with supplementation. The review is registered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…In the general population of Denmark (latitude 55–57°N) in 2012–2014, women had higher circulating 25(OH) D than men and were supplement users to a greater extent [ 24 ]. Observational studies and meta-analyses on populations from the wider European territories and in North America, Japan, and Australia have shown that high vitamin D level may lower CRC risk [ 1 , 2 , 25 , 26 ] and improve prognosis [ 3 , 4 , 27 30 ]. A prospective study in the United States in patients with metastatic CRC on first-line systemic therapy revealed that those randomized to high-dose vitamin D supplementation had better outcome than the control patient group given a standard vitamin D dose [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population of Denmark (latitude 55–57°N) in 2012–2014, women had higher circulating 25(OH) D than men and were supplement users to a greater extent [ 24 ]. Observational studies and meta-analyses on populations from the wider European territories and in North America, Japan, and Australia have shown that high vitamin D level may lower CRC risk [ 1 , 2 , 25 , 26 ] and improve prognosis [ 3 , 4 , 27 30 ]. A prospective study in the United States in patients with metastatic CRC on first-line systemic therapy revealed that those randomized to high-dose vitamin D supplementation had better outcome than the control patient group given a standard vitamin D dose [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence over the past decades supports that vitamin D has a beneficial effect on colorectal cancer (CRC) development and outcome [ 1 4 ]. The primary circulating form of vitamin D, 25-hydroxyvitamin D [25(OH) D], is mainly dependent on the exposure to ultraviolet B solar radiation, and levels are therefore depleted during the winter season at high latitudes unless the dietary supplementation is adequate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even more pronounced preventive effects of vitamin D 3 supplementation on cancer progression than reported by the VITAL study might be expected in studies focusing on cancer patients with 25(OH)D levels <20 ng/mL. Vitamin D insufficiency and deficiency are common among cancer patients [ 21 ], and preliminary results of randomized trials of vitamin D 3 supplementation for cancer patients showed encouraging results, although they were mostly underpowered [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from these premises, other studies focused on the potential usefulness of vitamin D supplementation to improve CRC patient management. A systematic review with a meta-analysis of randomized controlled trials by Vaughan-Shaw et al examined the effect of vitamin D supplementation on survival outcomes in patients with CRC, concluding that supplementation imparts a 30% reduction in adverse survival outcomes overall, with a 24% reduction in CRC-specific death and a 33% reduction in disease progression or death [ 164 ]. Overall, vitamin D seems to have a promising role as a prognostic factor for CRC patients’ outcome and an easy element to improve in case of deficiency, being widely available and cheap to apply in large populations at all ages.…”
Section: Micronutrients and Molecular Tuning Of Colorectal Carcinogenesismentioning
confidence: 99%